2022
DOI: 10.34739/zn.2021.56.04
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies or Capital Markets. Comparative Analysis of Investment Efficiency in 2011-2020

Abstract: Cryptocurrencies have become an important element of the global financial system and a frequent investment tool in the last decade. The aim of this paper is to compare the efficiency of investments in the cryptocurrency market with investments in global capital markets. The study used the quotations of the analyzed instruments in the years 2011-2020. The investment efficiency was estimated using Sharpe and Sortino ratios. Research has shown that investments in cryptocurrencies were the most effective. They bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…This present study is interested in two specific strands of literature. The first focuses on determining whether cryptocurrency is a diversifier, hedge, or safe haven for the traditional financial system (Bouri et al 2020;Okorie and Lin 2020;Kumah and Mensah 2020;Majdoub et al 2021;Kozak and Gajdek 2021;Lavelle et al 2021;Iyer 2022).…”
Section: Cryptocurrency Market Interconnectedness With Traditional Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…This present study is interested in two specific strands of literature. The first focuses on determining whether cryptocurrency is a diversifier, hedge, or safe haven for the traditional financial system (Bouri et al 2020;Okorie and Lin 2020;Kumah and Mensah 2020;Majdoub et al 2021;Kozak and Gajdek 2021;Lavelle et al 2021;Iyer 2022).…”
Section: Cryptocurrency Market Interconnectedness With Traditional Fi...mentioning
confidence: 99%
“…Several studies revealed that cryptocurrency acts as a diversifier to other stock portfolios and traditional financial instruments, given the low but positive correlation between instruments from the two markets (Okorie and Lin 2020;Majdoub et al 2021;Kozak and Gajdek 2021;Lavelle et al 2021). Most of these studies found cryptocurrency to have higher returns with higher risk.…”
Section: Cryptocurrency Market Interconnectedness With Traditional Fi...mentioning
confidence: 99%